Design for disassembly: Using temporary fabrication for land politics in the Negev. (June 2020) - Nathansohn, Nof; Mason, Molly; White, David Allen; Ebdy, Hugh Timothy; Yacoby, Yaara; Sharabi, Hila; Sass, Lawrence
Political conflicts have increasingly displaced people from their homes, necessitating various forms of temporary structures and housing. However, these shelters are often one-size-fits-all and do not take into account the individual requirements, family structures, or cultural needs of these communities. This article explores how digital fabrication can be used to empower disenfranchised communities to act as their own architects. Because the police demolish the structures in Al Araqib every 3 weeks, the residents have to rebuild their structures, and appropriate architecture as a resistance tool, and not only as a housing solution. This circumstance allows us to develop a structure designed primarily for the condition of rapid disassembly that can additionally be produced with a low-tech setup of a mobile computer numerical control router. Through this case study with the Bedouin village Al Araqib in the Negev Desert, we introduce the term community-specific design, present our methodology for designing and fabricating a temporary structure in collaboration with the community, and outline the logistics for a future mobile infrastructure. Beyond aiding the Bedouin's fight for justice, our intention as designers, acutely aware of the power of technology and architecture, is to harness both physical and digital tools in an effort to create innovative systems that can be leveraged by unrecognized populations struggling for cultural survival.